2004
DOI: 10.1037/0882-7974.19.3.541
|View full text |Cite
|
Sign up to set email alerts
|

The Associative Memory Deficit of Older Adults: Further Support Using Face-Name Associations.

Abstract: Previous studies have established an associative deficit hypothesis (Naveh-Benjamin, 2000), which attributes part of older adults' deficient episodic memory performance to their difficulty in creating cohesive episodes. In this article, the authors further evaluate this hypothesis, using ecologically relevant materials. Young and old participants studied name-face pairs and were then tested on their recognition memory for the names, faces, and the name-face pairs. The results extend the conditions under which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
257
10
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(296 citation statements)
references
References 25 publications
26
257
10
2
Order By: Relevance
“…They found larger agerelated decline for associative than for item memory, in agreement with the associative deficit hypothesis of ageing (Naveh-Benjamin, 2000). According to this hypothesis, an important cause of poor episodic memory performance in older adults is their deficiency in creating and retrieving associations between single information units, including associations between different items, item and its context or item features (NavehBenjamin, Brav, & Levy, 2007;Naveh-Benjamin, Guez, Kilb, & Reedy, 2004;Naveh-Benjamin, Hussain, Guez, & Bar-On, 2003). However, when separately examining hits (i.e., correct response to studied pairs) and false alarms to rearranged pairs (i.e., wrongly accepting a recombined pair in which both of the presented items were studied but not together), the authors found that age differences in associative memory were mainly driven by age differences in false alarms.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…They found larger agerelated decline for associative than for item memory, in agreement with the associative deficit hypothesis of ageing (Naveh-Benjamin, 2000). According to this hypothesis, an important cause of poor episodic memory performance in older adults is their deficiency in creating and retrieving associations between single information units, including associations between different items, item and its context or item features (NavehBenjamin, Brav, & Levy, 2007;Naveh-Benjamin, Guez, Kilb, & Reedy, 2004;Naveh-Benjamin, Hussain, Guez, & Bar-On, 2003). However, when separately examining hits (i.e., correct response to studied pairs) and false alarms to rearranged pairs (i.e., wrongly accepting a recombined pair in which both of the presented items were studied but not together), the authors found that age differences in associative memory were mainly driven by age differences in false alarms.…”
supporting
confidence: 66%
“…We assessed measures of binding (FaceÁName task; Naveh-Benjamin et al, 2004) and executivefrontal functioning (Wisconsin Card Sorting Task; Heaton, Chelune, Talley, Kay, & Curtis, 1993) to help relate age differences in false memory in the CR task more directly to the contrasting mechanisms. We did not assume that these covariate tasks purely measure binding or executive functioning, respectively.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Using a joint memory paradigm requiring recognition of items and associations between item pairs (cf. Humphreys, 1976), Naveh-Benjamin and colleagues (Naveh-Benjamin, 2000;Naveh-Benjamin, Brav, & Levy, 2007;Naveh-Benjamin et al, 2004;Naveh-Benjamin, Guez, & Marom, 2003;Naveh-Benjamin, Hussain, et al, 2003) consistently demonstrated that older adults showed deficits in encoding and retrieving associations among items. This decrease in the ability to remember compound information could not be attributed solely to older adults' deficit in remembering individual items, as negative age differences in item recognition memory were negligible and/or controlled for.…”
Section: Piecing Together Life-span Age Differences In the Associativmentioning
confidence: 97%
“…Only four of these studies had comparable measures of both item and associative memory and were therefore able to demonstrate larger associative memory deficits than item memory deficits in older adults: Naveh- Benjamin et al (2004; and Bastin and Van der Linden (2005) did not associate the faces to novel stimuli so only half of the stimuli were novel; Bastin and Van der Linden (2006) used pairs of unrelated faces, but item memory age differences were probably restricted by ceiling effects (proportion correct for item recognition was 0.93 for both young and older adults), making the comparison between item and associative memory age deficits difficult to interpret.…”
Section: Novel Stimulimentioning
confidence: 99%